Opłaty związane z zanieczyszczeniem wód we Francji i w Polsce. Analiza porównawcza. - Mariański, Michał; Zębek, Elżbieta (PRAWO i WIĘŹ, 2025)
This paper is one element of a broader comparative study of fees related to environmental law. The subject of the analysis was limited to a specific type of fees, i.e. those related to water pollution in France and Poland. Such a selection of countries for comparative analysis made it possible to highlight certain differences in the scope of the discussion, which may prove to be an incentive, especially from the point of view of the Polish legislator, to reflect on possible legislative changes. The comparative method, which allows the analysis of the law in a broader aspect than just the national one, also made it possible to draw conclusions on the possible directions of changes in the general nature of the fees collected by environmental protection authorities at the national level